The effect of omega 3 fatty acid supplementation on HbA1c serum in geriatric patients with type 2 diabetes mellitus: an evidence-based case report - Marvin Marino; Lily Indriani Octovia (Indonesian Nutrition Association, 2020)
Background: The prevalence of diabetes mellitus as a non-communicable diseases increase annually. The global prevalence doubled from 4.7% to 8.5% in 1980 until 2016. Insulin resistance is the primary cause of type 2 diabetes mellitus. Polyunsaturated fatty acid has a contribution to membrane fluidity as well as the cell signaling system. The result of studies about the correlation between Omega-3 supplementation and blood glucose control in patients with type 2 diabetes is still inconsistent. Meanwhile, we considered to give a 86 year old woman with an uncontrolled type 2 diabetes omega-3 fatty acid supplementation for controlling her blood glucose. Thus, we performed an evidence-based case report to respond this problem.Objectives: To observe the effect of omega-3 supplementation on glycated hemoglobin (HbA1c) serum of type 2 diabetes mellitus patients. Methods: Electronic literature searching was performed with Cochrane®, Scopus®, and Pubmed®. Inclusion and exclusion criteria were applied by MeSH term and title/abstract with clinical trial as the study design. Critical appraisal was performed for eligible article.Results: There were three articles relevant with the eligibility criteria and clinical question. One study found that omega-3 supplementation did not give a significant effect on HbA1c. The other two studies. found that there were improvement on HbA1c and lipid profile in patients that consumed omega 3.Conclusions: Omega-3 supplementation has inconsistent results for the improvement of HbA1c. The omega-3 lowering effect of HbA1c depends on the source, dosage, and duration of supplementation.